Post-buckling analysis of Timoshenko beams with various boundary conditions under non-uniform thermal loading - Kocaturk, Turgut; Akbas, Seref Doguscan (TECHNO-PRESS, 2011)
This paper focuses on post-buckling analysis of Timoshenko beams with various boundary conditions subjected to a non-uniform thermal loading by using the total Lagrangian Timoshenko beam element approximation. Six types of support conditions for the beams are considered. The considered highly non-linear problem is solved by using incremental displacement-based finite element method in conjunction with Newton-Raphson iteration method. As far as the authors know, there is no study on the post-buckling analysis of Timoshenko beams under uniform and non-uniform thermal loading considering full geometric non-linearity investigated by using finite element method. The convergence studies are made and the obtained results are compared with the published results. In the study, the relationships between deflections, end rotational angles, end constraint forces, thermal buckling configuration, stress distributions through the thickness of the beams and temperature rising are illustrated in detail in post-buckling case.
Keywords: geometrical non-linearity; post-buckling analysis; total lagrangian finite element model; Timoshenko beam; non-uniform temperature rise; SLENDER ELASTIC RODS; 2ND-ORDER ANALYSIS; COLUMN STRUCTURES; DEFLECTION; STABILITY; EQUATIONS; SHEAR; Engineering